1994
DOI: 10.1128/jb.176.5.1427-1433.1994
|View full text |Cite
|
Sign up to set email alerts
|

The dsg gene of Myxococcus xanthus encodes a protein similar to translation initiation factor IF3

Abstract: The dsg mutants of Myxococcus xanthus are defective in fruiting body development and sporulation, yet they grow normally. The deduced amino acid sequence of the dsg gene product is 50 and 51% identical to the amino acid sequence of translation initiation factor IF3 of both Escherichia coli and Bacillus stearothermophilus, respectively. However, the Dsg protein has a carboxy-terminal extension of 66 amino acids, which are absent from its E. coli and B. stearothermophilus homologs. The Shine-Dalgarno sequence GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The amino acid sequences of Dsg and IF3 are 50% homologous throughout the length of IF3 (5). Dsg, however, extends 66 amino acids beyond the carboxy terminus of E. coli or B. stearothermophilus IF3.…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid sequences of Dsg and IF3 are 50% homologous throughout the length of IF3 (5). Dsg, however, extends 66 amino acids beyond the carboxy terminus of E. coli or B. stearothermophilus IF3.…”
Section: Resultsmentioning
confidence: 99%
“…Measurements were made in both red light (RL) and green light (GL). infCa mRNA levels were normalized by using ribosomal RNA values for each sample (13 signal (Dsg) plays a role in both translation initiation and developmental processes, such as controlling sporulation and fruiting body development (30,39). In the purple nonsulfur bacterium Rhodobacter sphaeroides, the IF3-like protein PifC influences the production of bacteriochlorophyll and photosynthetic complexes (40).…”
Section: Discussionmentioning
confidence: 99%
“…For another sporulating bacterium, Bacillus subtilis, Tipper et al (45) suggested that some components of the translational machinery, namely ribosomal proteins and elongation factor G, could play a specific role during the spore formation process. In agreement with this idea, Cheng et al (6) identified the lesions in a Myxococcus xanthus development-deficient strain displaying a mutation in dsg, encoding a protein similar to translation initiation factor IF3. Compared to IF3s from other species, the Myxococcus IF3 is much larger and bears a C-terminal extension which was shown to be necessary for developmental functions but not for viability, even though during vegetative growth, colonies were shown to be more compact and to be a darker tan color (19).…”
mentioning
confidence: 73%